2018
DOI: 10.4314/jasem.v22i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and morphological properties of glass fiber reinforced epoxy composites fabricated under varying degrees of hand lay-up techniques

Abstract: Abstract:In this paper, attempts were made to study the progression of fibre-matrix adhesion of five composite specimens taking into consideration the hand lay-up method of composite formation. The ampreg 21 epoxy resin was used as the matrix for the glass fibre-epoxy resin formation. E-Glass fibre was used as matrix reinforcement. The morphology and the XRD of these composites were examined. Key of the findings from the morphological analysis of these composites showed that the fractured surface of the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…Thus, tensile, impact and hardness strength were found to be substantially increasing with the addition of GFD in LLDPE. As a result, the mechanical properties attained for composites produced with our streamlined method at room temperature are in good agreement with those previously published in the literature [22,24,25,45].…”
Section: Mechanical Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, tensile, impact and hardness strength were found to be substantially increasing with the addition of GFD in LLDPE. As a result, the mechanical properties attained for composites produced with our streamlined method at room temperature are in good agreement with those previously published in the literature [22,24,25,45].…”
Section: Mechanical Characterizationsupporting
confidence: 90%
“…An E-glass fiber epoxy resin formation was prepared by Adekomaya et al using hand layup technique. They investigated and concluded a better dimensional stability for these composites through morphological and XRD analysis [24]. E-glass and coconut fibre loaded epoxy and polyester combinations were efficaciously framed by Hemanth et al They witnessed an improved mechanical properties with tensile strength of 40.53 MPa, impact strength of 5.75 J, flexural strength of 177.37 MPa and Hardness value of 68.2 Hrm considering E-glass fiber epoxy composites [25].…”
Section: Introductionmentioning
confidence: 99%
“…This typical behavior was found less critical with G‐0 composites, which may be due to the lower modulus and higher elongation at break of glass fibers in comparison with basalt fiber in the composites as shown in Figure 12B. Adekomaya et al, [ 59 ] reported that the development of cavities with glass fiber reinforced at 0° orientated epoxy composite indicating poor fiber matrix adhesion. Figure 12C depicts that the glass fiber is well surrounded by vinyl ester matrix and fracture is seen in the matrix rather than simply pull out of fiber.…”
Section: Resultsmentioning
confidence: 92%
“…The intensity of neat epoxy resin and alkali treated fiber composite (20% loading) is higher than untreated fiber composites with different fiber loadings (5%, 10%, 15%, and 20%). [ 37 ] This is because of the elimination of amorphous parts (hemicellulose & lignin) during alkali treatment. [ 38 ] The crystallinity index of neat epoxy resin is 80.04%.…”
Section: Resultsmentioning
confidence: 99%